Pengaruh Digital Marketing Dan Desain Produk Terhadap Volume Penjualan Industri Hasil Rumahan (Studi Pada Pelaku Industri Tas di Tanggulangin Sidoarjo) - Mirzatul Ummah; Rois Arifin; Muhammad Khoirul Anwarodin Brotosuharto (UNIVERSITAS ISLAM MALANG, 2022)
Abstract This study goals to know and analyse the effect of digital marketing and product desain to volume selling in home industry bag at tanggulangin, sidoarjo city. This population used all craftman bag kludan at tanggulangin, sidoarjo city with total 169 respondent. Meanwhile, all sample used 63 respondent. In study used analysis such as instrument test, classic assumption test, analysis multiple regression test, hypothesis test, and determination coefficient test (R2). Through this study it can be conclude that digital marketing has a positive effect and significant to volume selling, and product desain has a positive effect and significant to volume selling. Meanwhile this result was simultaneously that digital marketing and product desain has a positive effect and significant to volume selling in home industry bag at tanggulangin, sidoarjo city. Keywords : digital marketing, product desain, volume selling.